Peacebuilding in language education : innovations in theory and practice - Oxford, Rebecca L.; Gregersen, Tammy (Multilingual Matters, 2021)
"This book shares wisdom and strategies to help language teachers, teacher educators, and peace educators communicate peace, contribute to peace and weave peacebuilding into classrooms and daily life. The book's Language of Peace Approach and more than 50 creative activities nurture peacebuilding skills in students, educators and the community"-- Provided by publisher.
Keywords: Peace -- Study and teaching -- Activity programs.; English language -- Study and teaching -- Foreign speakers -- Activity programs.; Paix -- Étude et enseignement -- Méthodes actives.; LANGUAGE ARTS & DISCIPLINES / Study & Teaching.; English language -- Study and teaching -- Foreign speakers; Peace -- Study and teaching -- Activity programs